PENINGKATAN KETERAMPILAN MENULIS BAHASA INGGRIS SISWA PADA TEKS DESKRIPSI DENGAN MENGGUNAKAN STRATEGI ROUNDTABLE ( PENELITIAN TINDAKAN KELAS : PADA KELAS VIII MADRASAH TSANAWIYAH SWASTA TALANGBATU - HAMBALI, KHAIRUL UMAM (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is conducted in order to improve the writing skills of the grade eight students at Madrasah Tsanawiyah Swasta Talangbatu Tangkiang by using a roundtable strategy. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. This research consisted of two cycles and each cycle consisted of four steps, they were: Planning, Action, Observation, and Reflection. To collect and analyze the data, the researcher used the descriptive qualitative method. The qualitative data obtained by observing the teaching and learning process, interviewing the English teachers and the students of grade eight. The qualitative data were in the form of observation sheets, teaching journals and interview. The successful of criteria of this research were the students might be able to write the descriptive text through the successful of process. The results showed that the roundtable strategy can improve the students of eight grade of Madrasah Tsanawiyah Talangbatu Tangkiangâ€™s writing skill on descriptive text. The improvements could be seen in the teaching and learning process, participations, enthusiasm, understanding the material of descriptive text, and classroom circumstances became better. Â Keywords : CAR, Roundtable Strategy, Writing, Descriptive Text, Junior High School.